eHealth literacy level and its predictors among primary school teachers - Mehdi Khancolabi; Zahra Nowrozian; Reza Shahrabadi; Mitra Gharib; Hassan Saadati; Saeed Nowrouzian (BMC Public Health)
Abstract Background and aim The present study aims to investigate eHealth literacy and its related factors among primary school teachers in Sabzevar city. Method The current cross-sectional descriptive analytical study was conducted on 252 primary school teachers in Sabzevar city in 2021. The data collection tool included a three-part questionnaire. The first part included 21 demographic questions, the second part of the questionnaire included 8 questions regarding eHealth literacy, and the third part consisted of 10 questions created by the researcher to complete the standard questionnaire. Data analysis was performed using SPSS software and the statistical significance level was P ≤ 0.05. Results The mean scores of eHealth literacy of the teachers according to the standard and complete questionnaires were 25.44 ± 5.90 and 60.17 ± 10.17, respectively. There was a statistically significant difference in the eHealth literacy levels of the subjects according to the evaluation of the level of general health, regular physical activity, general knowledge in the field of health, the amount of using the Internet, the use of information related to health through social networks based on both questionnaires (standard/complete). For the standard and complete questionnaires, the multiple correlation coefficient values were 0.48 and 0.52, respectively. The adjustment coefficient value for both questionnaires (R2 Adjusted = 0.20). Conclusion The eHealth literacy of the teachers in this study was not appropriate. The mastery of cyberspace, the level of education, having traditional health literacy were among the most important factors affecting the improvement of teachers’ electronic health literacy.